Métrica para definição de pontos estáveis utilizando-se da Análise de Robustez no posicionamento por ponto preciso - Cavalheri, Emerson Pereira [UNESP] (2015)
Deformation monitoring of large structures or land surface, the displacement of the investigated points are usually obtained according to points located outside of the studied body and they are considered to be stable (reference points) in the analysis. If these constrained points, assumed as references, in reality are not stable the nal parameters will be directly in uenced by this consideration. To establish a reference network stable points must be found, i.e, those that least move over time. The instability or displacements in the point position with respect to time can be separated into two types: continental and local. The continental displacements treat the su ered motion by the station on the basis of the continental speed, that is, due to the plate movement that the point is locate. The local displacements are obtained as function of physical phenomena of the local geology, they may or may not have a pattern of variation. Local movements are the only of extreme interest in the de nition of stable points. Thus, this work proposes a strategy for classi cation of stable points by using these obtained displacements without the in uence of continental displacements in the station position. Based on coordinate time series obtained from the PPP (Precise Point Positioning) processing method with the GAPS (GPS Analysis and Positioning Software) software, comparing them to coordinates obtained from a velocity model, e.g., the VEMOS2009 (Velocity Model for South America and the Caribbean), is intended to de ne a metric for classi cation of stable points, where the Network Robustness Analysis is adopted as a statistical criterion for evaluation of the proposed mathematical model...